A high-strength, high-toughness, high-conductivity voltage-casting aluminum alloy and preparation method thereof
By adding rare earth element La and two solid solution atoms Zn and Li to the die-cast aluminum alloy, the high strength and high conductivity are achieved, and the problem that the prior art is difficult to meet the conductivity and strength requirements at the same time.
Patent Information
- Application Number
- CN202310587865.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-23
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2043-05-23
AI Technical Summary
Existing die-cast aluminum alloys are difficult to meet the needs of extremely high conductivity and high toughness characteristics at the same time, especially in applications such as motor rotors.
By adding rare earth element La to pure aluminum to form a diffuse second phase and introducing two solid-solution atoms Zn and Li, the lattice distortions of the two solid-solution atoms are canceled out with each other through the multi-solution design idea, thereby improving the strength and conductivity of the aluminum alloy.
It has achieved the dual needs of die-cast aluminum alloys in terms of extremely high conductivity (higher than 30MS/m) and high toughness characteristics (yield strength higher than 120MPa, tensile strength higher than 200MPa, elongation higher than 10%), meeting the dual needs of motor rotors and other parts.
Smart Images

Figure CN116623043B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal materials, and in particular to a high-strength, high-toughness and high-conductivity voltage-cast aluminum alloy and a preparation method thereof. Background Art
[0002] Die-cast aluminum materials are widely used in transportation, electronic communications and other fields due to their light weight, high strength and high conductivity, such as motor rotors for new energy vehicles. With the rapid development of new energy vehicles, higher requirements are placed on aluminum materials for motor rotors, that is, they must have extremely high conductivity (>30Ms / m) and high strength and toughness. The common high-conductivity cast aluminum alloys commonly used on the market are mostly Al-Si alloys, whose conductivity is about 25Ms / m, which is difficult to meet the requirements of motor rotors for high conductivity. The Chinese invention patent with application number 201410480808.4 discloses an alloy aluminum for motor rotors and a preparation method thereof. About 1.5wt.% of Mn elements and a small amount of Ti and Cr elements are added to pure aluminum. Although the strength of the aluminum alloy is improved, the conductivity of the aluminum material is reduced to about 16Ms / m, which also cannot meet the requirements. The Chinese invention patent with application number 202210127069.5 discloses an Al-Ni alloy, which can improve the strength of aluminum alloy while ensuring that the alloy has an electrical conductivity of about 28Ms / m (47.9% IACS), but this will also increase the energy consumption of the motor rotor; and the aluminum alloy involved has a conductivity of up to 33Ms / m (57% IACS), but its tensile strength is only 110MPa, which is difficult to meet the strength requirements of electronic rotors.
[0003] The Chinese invention patent 202010129226.7 previously applied by the inventor discloses a high-toughness and high-thermal-conductivity die-cast aluminum alloy and a preparation method thereof. By adding an appropriate amount of rare earth element La to pure aluminum, the high thermal conductivity of pure aluminum is maintained while significantly improving the strength of pure aluminum. Although the limiting solid solubility of La in the Al matrix is only 0.001795wt.%, it is very easy to react with Al to form fine dispersed Al 11 La 3 The second phase strengthens the grain boundary, but too high La content will make Al 11 La 3 The phase is significantly coarsened and blocky Al is generated. 11 La 3Phase, not only reduces the strengthening effect, but also greatly reduces the plasticity of the alloy; and too low La content cannot provide sufficient strength. In order to solve the above technical problems, the Chinese invention patent 202210540895.2 applied by the inventor discloses a high-strength and high-thermal conductivity die-cast aluminum alloy that can be strengthened by aging and a preparation method thereof. The aluminum alloy composition is: 6.0~8.0wt.% La, 2.5~4.0wt.% Zn, 0.5~1.0wt.% Mg, 0.1~0.5wt.% Cu, and the rest is Al and unavoidable impurities; the thermal conductivity and intracrystalline strength are significantly improved by pressure casting plus T5 aging heat treatment. However, the above technical solution still has many disadvantages: the addition of ordinary solid solution atoms will greatly increase the lattice distortion, thereby reducing the electrical conductivity of the aluminum alloy. Summary of the invention
[0004] In view of the deficiency that the existing die-cast aluminum alloy cannot simultaneously meet the extremely high electrical conductivity and high strength and toughness properties, the present invention proposes a high-strength, high-toughness and high-conductivity die-cast aluminum alloy and a preparation method thereof.
[0005] The objective of the present invention is achieved through the following technical solutions:
[0006] A high-strength, high-toughness and high-conductivity die-cast aluminum alloy comprises: 3.0-7.0 wt. % La, 2.0-5.0 wt. % Zn, 0.2-0.5 wt. % Li, and the remainder is Al and inevitable impurities.
[0007] Furthermore, the composition of the die-casting aluminum alloy includes: 4.0-6.0 wt. % La, 2.0-5.0 wt. % Zn, 0.2-0.5 wt. % Li, and the balance is Al and inevitable impurities.
[0008] The composition of the die-casting aluminum alloy includes: 4.0-6.0 wt. % La, 3.0-4.5 wt. % Zn, 0.3-0.45 wt. % Li, and the balance is Al and inevitable impurities.
[0009] The mass ratio of Zn to Li in the die-casting aluminum alloy is 9.5-9.8.
[0010] The microstructure of the die-cast aluminum alloy is composed of La and Al. 11 La 3 Zn and Li exist in the form of solid solution atoms.
[0011] Furthermore, the present invention also provides a method for preparing the die-cast aluminum alloy, comprising the following steps:
[0012] S1. Weigh raw materials of pure aluminum, Al-La master alloy, Al-Zn master alloy and Al-Li master alloy according to the proportion;
[0013] S2, after heating and melting pure aluminum and Al-La master alloy, controlling the temperature at 690-710° C., adding Al-Zn master alloy and Al-Li master alloy, and continuing to melt to obtain alloy melt;
[0014] S3, heating the alloy melt in step S2 to 730-750°C, adding a refining agent for refining and slag removal, then reducing the melt temperature to 720-730°C and keeping the temperature for 20-30 minutes;
[0015] S4, when the melt temperature in step S3 is stabilized at 700-710°C, die casting is performed using a mold.
[0016] A pre-processing step is also included between steps S1 and S2, and the pre-processing step includes:
[0017] A. Grind and clean the raw materials of pure aluminum, Al-La master alloy, Al-Zn master alloy and Al-Li master alloy;
[0018] B. Preheat the raw materials after grinding and cleaning.
[0019] The preheating method in step B includes: preheating at 200-250° C. for 3-4 hours to remove water vapor.
[0020] In step S4, a die-casting machine is used for die casting, the temperature of the mold is 200-250° C., the slow injection speed is 0.25-0.5 m / s, the fast injection speed is 2.4-3 m / s, and the casting pressure is 75-80 MPa.
[0021] The mold is a metal mold.
[0022] The refining agent of the present invention comprises at least one of manganese chloride, hexachloroethane and carbon tetrachloride.
[0023] The refining agent in the technical solution of the present invention can also be a refining agent commonly used in the art.
[0024] The core idea involved in the technical solution of the present invention is: in die-cast aluminum alloys, alloying is the main way to improve strength, among which the alloy elements in the form of fine dispersed second phases can significantly improve the strength of the alloy, but the dispersed second phases formed in the die-cast aluminum alloys mostly exist near the grain boundaries, resulting in extremely low strength of the aluminum matrix; and the introduction of a large amount of the same alloying element will significantly coarsen the second phase and affect the strengthening effect, so it is necessary to introduce a certain amount of solid solution atoms into the aluminum alloy to improve the strength. The electrical conductivity of die-cast aluminum alloys is mainly related to the distortion caused by the alloying elements. Under normal circumstances, the existence of elements in the form of solid solution atoms will produce a large lattice distortion, increase the probability of electron scattering, and thus significantly reduce the electrical conductivity of the aluminum alloy. Therefore, conventional high-conductivity aluminum alloy designs will avoid solid solution atoms as much as possible, which makes it difficult to take into account both conductivity and strength. The present invention intends to strengthen pure aluminum by adding rare earth elements to pure aluminum to form a dispersed second phase, and further introduce two solid solution atoms, one of which has an atomic radius larger than the atomic radius of aluminum, and the other has an atomic radius smaller than the atomic radius of aluminum, such as Figure 1 As shown, the addition of a single solid solution atom will significantly increase the lattice distortion. However, by designing the ratio of the two solid solution atoms, the lattice distortions caused by the two solid solution atoms can offset each other, thereby greatly improving the strength of the aluminum alloy while maintaining its high conductivity.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] (1) The die-cast aluminum alloy provided by the present invention has both extremely high electrical conductivity and high strength and toughness, wherein the electrical conductivity is higher than 30MS / m, the yield strength is higher than 120MPa, the tensile strength is higher than 200MPa, and the elongation is higher than 10%;
[0027] (2) The present invention uses the design concept of multi-solid solution to achieve the mutual cancellation of the lattice distortion of the solid solution atoms, thereby greatly improving the strength of the die-cast aluminum alloy while maintaining high conductivity, thereby solving the problem of low strength caused by the difficulty of solid solution strengthening of ordinary high-conductivity die-cast aluminum alloys;
[0028] (3) The die-cast aluminum alloy provided by the present invention can meet the dual requirements of high strength and high conductivity for motor rotors and other parts;
[0029] (4) In order to make up for the defects of the prior patent 202210540895.2, the present invention introduces two solid solution atoms, one large and one small, into the aluminum alloy. Considering that the Al atomic radius is 143pm, the Li atomic radius is 152pm, and the Zn atomic radius is 133pm, and both Li and Zn have a large solid solubility in the aluminum matrix (the limit solid solubility of Li in the Al matrix is 4.0wt.%, and the solid solubility of Zn in the Al matrix is greater than 30wt.%), if Li and Zn solid solution atoms are introduced into the aluminum matrix at the same time, it is possible to achieve mutual offset of lattice distortion, thereby maintaining the high conductivity of the alloy. After further research, it was found that when the solid solution atomic ratio Zn:Li=1.03, that is, the solid solution mass ratio Zn:Li=9.62, the average volume of the two elements Zn and Li is the same as that of the Al matrix. Therefore, if Zn and Li are added at the same ratio, it is very likely to offset the lattice distortion caused by the solid solution atoms, and significantly improve the strength of the alloy while maintaining the high conductivity of the aluminum alloy. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:
[0031] Figure 1 Schematic diagram of lattice distortion caused by solid solution of Zn and Li in Al matrix, where (a) no solid solution; (b) solid solution Zn:Li is much less than 1.03; (c) solid solution Zn:Li is much greater than 1.03; (d) solid solution Zn:Li is equal to 1.03;
[0032] Figure 2 The microstructure and schematic diagram of the die-cast Al-6La-3.0Zn-0.31Li aluminum alloy in Example 1 of the present invention; (a) microstructure diagram; (b) schematic diagram;
[0033] Figure 3 The microstructure and schematic diagram of the die-cast Al-2La-3.0Zn-0.31Li aluminum alloy of comparative example 1 of the present invention; (a) microstructure diagram; (b) schematic diagram;
[0034] Figure 4 The microstructure and schematic diagram of the die-cast Al-10La-3.0Zn-0.31Li aluminum alloy of comparative example 2 of the present invention; (a) microstructure diagram; (b) schematic diagram. DETAILED DESCRIPTION
[0035] The present invention is described in detail below in conjunction with embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, some adjustments and improvements can also be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0036] Example 1
[0037] Al-6La-3.0Zn-0.31Li high strength, toughness and high conductivity voltage cast aluminum alloy
[0038] This embodiment provides 30 kg of Al-6La-3.0Zn-0.31Li high-strength, high-toughness and high-conductivity voltage-cast aluminum alloy (i.e., containing 6.0wt.% La, 3.0wt.% Zn, 0.31wt.% Li, and the rest being Al and unavoidable impurities) and its preparation method.
[0039] Step 1: Ingredients: weigh raw materials pure aluminum, Al-La master alloy, Al-Zn master alloy and Al-Li master alloy according to the proportion;
[0040] Step 2: Preheating: First, the raw materials of pure aluminum, Al-La master alloy, Al-Zn master alloy and Al-Li master alloy are polished and cleaned, and then preheated at 220°C for 3 hours to remove moisture;
[0041] Step 3: Melting: Put the preheated pure aluminum and Al-La master alloy into a resistance furnace for heating and melting. When all are melted, control the temperature at 700°C and add Al-Zn master alloy and Al-Li master alloy to continue melting.
[0042] Step 4: Refining: Heat the melted alloy to 740°C, add refining agent to refine and remove slag, then reduce the melt temperature to 720°C and keep it warm for 30 minutes;
[0043] Step 5: Die casting: After the refined melt temperature is cooled to 700℃, it is die-casted on a die-casting machine. The temperature of the metal mold is 210℃, the slow injection speed is 0.25m / s, the fast injection speed is 2.4m / s, and the casting pressure is 75MPa.
[0044] The microstructure and schematic diagram of the alloy prepared in this embodiment are shown in FIG. Figure 2 As shown ( Figure 2 (a) microstructure; (b) schematic diagram), containing a moderate amount of needle-shaped Al at the grain boundary 11 La 3 The second phase and the α-Al matrix of Zn and Li co-solid solution, in which the atomic ratio of Zn and Li in the solid solution is 1.03, the schematic diagram of its lattice distortion is as follows Figure 1(d) is shown. Figure 1 Based on the pure aluminum matrix lattice shown in (a), the lattice distortion produced after solid solution is extremely small and is expected to have little effect on the conductivity.
[0045] Example 2
[0046] Al-4La-3.0Zn-0.31Li high strength, toughness and high conductivity voltage cast aluminum alloy
[0047] This embodiment provides 30 kg of Al-4La-3.0Zn-0.31Li high-strength, high-toughness and high-conductivity voltage-cast aluminum alloy (i.e., containing 4.0wt.% La, 3.0wt.% Zn, 0.31wt.% Li, and the rest being Al and unavoidable impurities) and its preparation method.
[0048] Step 1: Ingredients: weigh raw materials pure aluminum, Al-La master alloy, Al-Zn master alloy and Al-Li master alloy according to the proportion;
[0049] Step 2: Preheating: First, the raw materials of pure aluminum, Al-La master alloy, Al-Zn master alloy and Al-Li master alloy are polished and cleaned, and then preheated at 220°C for 3 hours to remove moisture;
[0050] Step 3: Melting: Put the preheated pure aluminum and Al-La master alloy into a resistance furnace for heating and melting. When all are melted, control the temperature at 700°C and add Al-Zn master alloy and Al-Li master alloy to continue melting.
[0051] Step 4: Refining: Heat the melted alloy to 740°C, add refining agent to refine and remove slag, then reduce the melt temperature to 720°C and keep it warm for 30 minutes;
[0052] Step 5: Die casting: After the refined melt temperature is cooled to 700℃, it is die-casted on a die-casting machine. The temperature of the metal mold is 210℃, the slow injection speed is 0.25m / s, the fast injection speed is 2.4m / s, and the casting pressure is 75MPa.
[0053] The microstructure of the alloy obtained in this embodiment is basically the same as that in Example 1, except that the Al 11 La 3 Slightly less.
[0054] Example 3
[0055] Al-4La-4.0Zn-0.42Li high strength, toughness and high conductivity voltage cast aluminum alloy
[0056] This embodiment provides 30 kg of Al-4La-4.0Zn-0.42Li high-strength, high-toughness and high-conductivity voltage-cast aluminum alloy (i.e., containing 4.0wt.% La, 4.0wt.% Zn, 0.42wt.% Li, and the rest being Al and unavoidable impurities) and its preparation method.
[0057] Step 1: Ingredients: weigh raw materials pure aluminum, Al-La master alloy, Al-Zn master alloy and Al-Li master alloy according to the proportion;
[0058] Step 2: Preheating: First, the raw materials of pure aluminum, Al-La master alloy, Al-Zn master alloy and Al-Li master alloy are polished and cleaned, and then preheated at 220°C for 3 hours to remove moisture;
[0059] Step 3: Melting: Put the preheated pure aluminum and Al-La master alloy into a resistance furnace for heating and melting. When all are melted, control the temperature at 700°C and add Al-Zn master alloy and Al-Li master alloy to continue melting.
[0060] Step 4: Refining: Heat the melted alloy to 740°C, add refining agent to refine and remove slag, then reduce the melt temperature to 720°C and keep it warm for 30 minutes;
[0061] Step 5: Die casting: After the refined melt temperature is cooled to 700℃, it is die-casted on a die-casting machine. The temperature of the metal mold is 210℃, the slow injection speed is 0.25m / s, the fast injection speed is 2.4m / s, and the casting pressure is 75MPa.
[0062] The microstructure of the alloy obtained in this embodiment is basically the same as that in Embodiment 2, except that there are more solid solution atoms in the aluminum matrix, but the solid solution atomic ratio still satisfies Zn:Li=1.03.
[0063] Comparative Example 1
[0064] Al-2La-3.0Zn-0.31Li aluminum alloy
[0065] Compared with Example 1, the amount of La used in this comparative example is reduced. The preparation method is the same as that in Example 1.
[0066] This comparative example provides 30 kg of Al-2La-3.0Zn-0.31Li high-strength, high-toughness and high-conductivity voltage-cast aluminum alloy (i.e., containing 2.0wt.% La, 3.0wt.% Zn, 0.31wt.% Li, and the rest being Al and unavoidable impurities) and its preparation method.
[0067] The microstructure and schematic diagram of the alloy prepared in this comparative example are shown in Figure 3 As shown ( Figure 3(a) microstructure; (b) schematic diagram), contains fewer needle-shaped Al at the grain boundaries 11 La 3 The second phase and the α-Al matrix of Zn and Li co-solid solution. Compared with Example 1, the Al 11 La 3 The second phase is less and the strengthening effect is expected to be poor.
[0068] Comparative Example 2
[0069] Al-10La-3.0Zn-0.31Li aluminum alloy
[0070] Compared with Example 1, the amount of La used in this comparative example is increased. The preparation method is the same as that in Example 1.
[0071] This comparative example provides 30 kg of Al-10La-3.0Zn-0.31Li high-strength, high-toughness and high-conductivity voltage-cast aluminum alloy (i.e., containing 10.0wt.% La, 3.0wt.% Zn, 0.31wt.% Li, and the rest being Al and unavoidable impurities) and its preparation method.
[0072] The microstructure and schematic diagram of the alloy prepared in this comparative example are shown in Figure 4 As shown ( Figure 4 (a) microstructure; (b) schematic diagram), contains a large number of needle-shaped Al 11 La 3 The second phase, the large block of Al located in the crystal 11 La 3 The second phase and the α-Al matrix of Zn and Li co-solid solution. Compared with Example 1, large blocks of Al 11 La 3 Second phase, needle-shaped Al at the grain boundary 11 La 3 The phase is more and obviously coarsened, and the elongation is expected to be poor and the conductivity is not high.
[0073] Comparative Example 3
[0074] Al-6La-6.0Zn-0.31Li aluminum alloy
[0075] Compared with Example 1, the amount of Zn used in this comparative example is increased. The preparation method is the same as that in Example 1.
[0076] This comparative example provides 30 kg of Al-6La-6.0Zn-0.31Li high-strength, high-toughness and high-conductivity voltage-cast aluminum alloy (i.e., containing 6.0wt.% La, 6.0wt.% Zn, 0.31wt.% Li, and the rest being Al and unavoidable impurities) and its preparation method.
[0077] The microstructure morphology of the alloy prepared in this embodiment is roughly the same as that in embodiment 1, except that the ratio of Zn:Li in the Al matrix is much larger than 1.03. The schematic diagram of the lattice distortion is shown in FIG. Figure 1 Compared with Example 1, the lattice distortion is larger and the conductivity is expected to decrease significantly.
[0078] Comparative Example 4
[0079] Al-6La-3.0Zn-0.7Li aluminum alloy
[0080] Compared with Example 1, the amount of Li used in this comparative example is increased. The preparation method is the same as that in Example 1.
[0081] This comparative example provides 30 kg of Al-6La-3.0Zn-0.7Li high-strength, high-toughness and high-conductivity voltage-cast aluminum alloy (i.e., containing 6.0wt.% La, 3.0wt.% Zn, 0.7wt.% Li, and the rest being Al and unavoidable impurities) and its preparation method.
[0082] The microstructure morphology of the alloy prepared in this embodiment is roughly the same as that in embodiment 1, except that the ratio of Zn:Li in the Al matrix is much smaller than 1.03. The schematic diagram of the lattice distortion is shown in FIG. Figure 1 Compared with Example 1, the lattice distortion is larger and the conductivity is expected to decrease significantly.
[0083] Performance Testing
[0084] The high-strength, toughness and high-conductivity die-cast aluminum alloys prepared in the above-mentioned embodiments 1-3 and the ordinary aluminum alloys prepared in comparative examples 1-4 were tested for mechanical properties and electrical conductivity. The tensile performance test was carried out on a Zwick Z100 universal material testing machine, with a tensile rate of 1 mm / min and a sample marking length of 50 mm; the electrical conductivity test was carried out using a Sigma 2008 digital eddy current metal conductivity meter, and the sample was a disc with a diameter of 20 mm and a thickness of 3 mm. Each data point is the average value of 6 valid tests, and the performance test results are listed in Table 1. It can be seen from Table 1 that the electrical conductivity of the die-cast aluminum alloy prepared in embodiments 1-3 is higher than 30MS / m, the yield strength is higher than 120MPa, the tensile strength is higher than 200MPa, and the elongation is higher than 10%. Therefore, the die-cast aluminum alloy provided by the present invention has both high strength and toughness characteristics under the premise of having extremely high electrical conductivity, and can meet the requirements of electrical conductivity and mechanical properties of components such as motor rotors.
[0085] Table 1 Test results of electrical conductivity and mechanical properties of die-cast aluminum alloy
[0086] Alloy Material Conductivity (MS / m) Yield strength(MPa) Tensile strength(MPa) Elongation(%) Example 1 30.2 152 235 10.3 Example 2 31.9 125 207 13.6 Example 3 31.2 139 220 12.5 Comparative Example 1 33.6 91 173 17.1 Comparative Example 2 26.2 198 282 5.3 Comparative Example 3 27.9 178 261 7.7 Comparative Example 4 27.8 162 250 8.7
[0087] In contrast, the La content in Comparative Example 1 is too low, and the second phase strengthening effect is poor, so its strength is low; the La content in Comparative Example 2 is too high, resulting in Al 11 La 3 Coarsening and bulk Al 11 La 3 The generation of Zn:Li in Comparative Example 3 causes the decrease of alloy conductivity and the significant reduction of elongation; in Comparative Example 3, Zn:Li is much greater than 1.03, resulting in excessive solid-dissolved Zn atoms in the aluminum matrix, which is easy to cause significant lattice distortion, thereby significantly reducing the electrical conductivity of the alloy; in Comparative Example 4, Zn:Li is much less than 1.03, resulting in excessive solid-dissolved Li atoms in the aluminum matrix, which is easy to cause significant lattice distortion, thereby significantly reducing the electrical conductivity of the alloy.
[0088] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.
Claims
1. A high-strength, high-toughness, high-conductivity voltage-cast aluminum alloy, characterized in that: The composition of the die-casting aluminum alloy is: 3.0-7.0wt.% La, 2.0-5.0wt.% Zn, 0.2-0.5wt.% Li, and the balance is Al and unavoidable impurities; The mass ratio of Zn to Li in the die-casting aluminum alloy is 9.5-9.8; The microstructure of the die-cast aluminum alloy is composed of La and Al. 11 La3 exists in the form of solid solution atoms while Zn and Li exist in the form of solid solution atoms; The die-cast aluminum alloy is prepared by a method comprising the following steps: S1. Weigh raw materials of pure aluminum, Al-La master alloy, Al-Zn master alloy and Al-Li master alloy according to the proportion; S2, after heating and melting pure aluminum and Al-La master alloy, controlling the temperature at 690-710° C., adding Al-Zn master alloy and Al-Li master alloy, and continuing to melt to obtain alloy melt; S3, heating the alloy melt in step S2 to 730-750°C, adding a refining agent for refining and slag removal, then reducing the melt temperature to 720-730°C and keeping the temperature for 20-30 minutes; S4, when the melt temperature in step S3 is stabilized at 700-710°C, die casting is performed on a die casting machine using a mold; The high-strength, toughness and high-conductivity voltage-cast aluminum alloy has an electrical conductivity higher than 30MS / m, a yield strength higher than 120MPa, a tensile strength higher than 200MPa and an elongation higher than 10%.
2. The high-strength, high-toughness, high-conductivity voltage-cast aluminum alloy according to claim 1, characterized in that: The composition of the die-casting aluminum alloy is: 4.0-6.0wt.% La, 2.0-5.0wt.% Zn, 0.2-0.5wt.% Li, and the balance is Al and inevitable impurities.
3. The high-strength, high-toughness, high-conductivity voltage-cast aluminum alloy according to claim 1, characterized in that: The composition of the die-casting aluminum alloy is: 4.0-6.0wt.% La, 3.0-4.5wt.% Zn, 0.3-0.45wt.% Li, and the balance is Al and inevitable impurities.
4. The high-strength, high-toughness, high-conductivity voltage-cast aluminum alloy according to claim 1, characterized in that: A pre-processing step is also included between steps S1 and S2, and the pre-processing step includes: A. Grind and clean the raw materials of pure aluminum, Al-La master alloy, Al-Zn master alloy and Al-Li master alloy; B. Preheat the raw materials after grinding and cleaning.
5. The high-strength, high-toughness, high-conductivity voltage-cast aluminum alloy according to claim 4, characterized in that: The preheating method in step B includes: preheating at 200-250° C. for 3-4 hours to remove water vapor.
6. The high-strength, high-toughness, high-conductivity voltage-cast aluminum alloy according to claim 5, characterized in that: In step S4, die casting is performed on a die casting machine using a mold, the temperature of the mold is 200-250° C., the slow injection speed is 0.25-0.5 m / s, the fast injection speed is 2.4-3 m / s, and the casting pressure is 75-80 MPa.
7. The high-strength, high-toughness, high-conductivity voltage-cast aluminum alloy according to claim 6, characterized in that: The mold is a metal mold.
Citation Information
Patent Citations
Aluminum alloy for motor rotor and casting method thereof
CN104232959A
High-toughness high-heat-conduction die-casting aluminum alloy and preparing method thereof
CN111321324A
Preparation method of high-strength high-thermal-conductivity high-electric-conductivity high-pressure cast aluminum alloy
CN114427047A
Al-Zn-Mg series aluminum alloy profile material and preparing method thereof
CN108642348A
High-strength high-thermal-conductivity die-casting aluminum alloy capable of being subjected to aging strengthening and preparation method thereof
CN114836656A